Pengaruh Inovasi Layanan Aplikasi dan Kreativitas Pemasaran Terhadap Peningkatan Penjualan Produk Makaroni Krenyesss Indonesia di Lombok Tengah Kecamatan Praya Timur - Nidaul Izzah; Chairul Anwar (JAMBIS : Jurnal Administrasi Bisnis, 2023)
This study aims to determine the effect of Application Service Innovation and marketing creativity to increase sales of macaroni products Krenyesss Indonesia in Central Lombok district Praya Timur. Quantitative research methods, with a sample of 100 respondents. Sampling technique using saturated sampling technique. Data collection techniques using questionnaires that have been tested for validity and reliability.The results showed that application service innovation (X1) and marketing creativity (X2) simultaneously affect the increase in sales (Y). Application Service Innovation variable (X1) that affects the increase in sales (Y) is the product has, while the marketing creativity variable (X2) that affects the increase in sales (Y).